Pengaruh Komik Digital Di Instagram Sebagai Media Kampanye Politik - ARIN RISKI ASTARIA; Fitriyah - - (Journal of Politic and Government Studies, 2020)
The 2019 presidential election was enlivened by old faces, namely Joko Widodo and Prabowo. The striking difference is that during this period, there was a new